2018
DOI: 10.1002/slct.201702780
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Based Composite Materials for Advanced Supercapacitors

Abstract: Zinc oxide based composite materials show advantages such as low cost, environmental protection, good electrochemical reversibility, high specific capacitance, high power density, high energy density, good cycling stability and simple preparation, which makes them promising materials for advanced supercapacitors. Based on the most advanced research, we present recent findings in the investigation, discussion and challenges related to various kinds of zinc oxide based composite materials, such as zinc oxide/car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 178 publications
(221 reference statements)
0
29
0
Order By: Relevance
“…This correlates well with that observed in several reports in the literature. 101,102 When 1 mM ferrocyanide is added to the electrolyte, well-dened waves of redox activity of diffusing species appear in both CVs (solid lines in Fig. 8).…”
Section: Electrochemical Characterisationmentioning
confidence: 96%
“…This correlates well with that observed in several reports in the literature. 101,102 When 1 mM ferrocyanide is added to the electrolyte, well-dened waves of redox activity of diffusing species appear in both CVs (solid lines in Fig. 8).…”
Section: Electrochemical Characterisationmentioning
confidence: 96%
“…8,9 Very recently, it was reported that ZnO-based composite electrode materials can provide good electrochemical reversibility, high specic capacitance, high power density, high energy density, and good cycling stability, which makes them promising materials for advanced supercapacitors. 10 In particular, ZnO is a highly defective wide band-gap semiconductor and a luminescent material, in which the defect centers play a vital role in its ionic and electronic transport properties. Conceivably, some of the possible intrinsic defect centers in ZnO are: (i) zinc vacancies, (ii) zinc on interstitial sites, (iii) oxygen on interstitial sites, and (iv) oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…A transparent ultrathin ERGO layer on the top of ZnO nanostructures is achieved by electrochemical reduction of a thin graphene oxide (GO) layer and clearly observed in Figure 1C. [11,32,33] Additionally, both the upper and lower surfaces of ERGO layer are accessible to electrolyte, offering a higher SSA for the electrochemical processes. [11,32,33] Additionally, both the upper and lower surfaces of ERGO layer are accessible to electrolyte, offering a higher SSA for the electrochemical processes.…”
Section: Resultsmentioning
confidence: 99%
“…

with various functional nanomaterials offering synergic properties, such as metal oxides, [5] conducting polymers [2] or carbon materials. [6][7][8][9][10][11][12] The combination of carbon materials with ZnO offers the benefits of both the electrical double layer (EDL) capacitance of the carbon materials with large specific surface area (SSA) and the faradaic contribution of the ZnO, thereby optimizing the electrochemical performance of the ZnO-based SCs. [8] Among carbon materials, graphene has spurred significant interest in electrochemical energy storage due to its high SSA, superior electronic conductivity and chemical resilience.

…”
mentioning
confidence: 99%